Women's participation in the Olympic Games - Albu, S. (Science, Movement & Health, 2026)
The participation of women in this major sporting event, the Olympic Games, was by no means a certainty, nor did it come without serious efforts on the part of the feminist movement. The improvement of the status of women occurred slowly, and women had to overcome numerous barriers. No matter how liberal and progressive society had become, women had to overcome a series of obstacles, one after another. The same happened with the fight for social rights, for the right to vote, or for the right to practice all sports and participate in the Olympic Games.